Improving Mathematics Learning Outcomes through Learning Cycle Development - Belman Mangapul R Horbo; Arif Rahman; Yumiati Yumiati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to describe about: (1) development of valid learning cycle teaching materials for improving student mathematics learning outcomes in grade VIII SMP North Tapanuli Regency, (2) development of practical learning cycle teaching materials for improving student mathematics learning outcomes in grade VIII SMP North Tapanuli Regency, (3) development of effective learning cycle teaching materials for improving student mathematics learning outcomes in grade VIII SMP North Tapanuli Regency, and (4) improving students' mathematics learning outcomes using teaching materials based on the learning cycle method developed in grade VIII of SMP North Tapanuli Regency. The subjects in this study are grade VIII students of SMP Negeri 2 Parmonangan for the 2021/2022 academic year. The subjects in this study are grade VIII students of SMP Negeri 2 Parmonangan for the 2021/2022 academic year. The object of this research is mathematics teaching materials developed based on learning cycle learning methods to improve mathematics learning outcomes of Pythagorean Theorem material. Research using the Plomp development model consists of investigation, design, realization/construction, test, evaluation and revision, and implementation phases. The product test consists of Teaching Material Validity Data Analysis consisting of three linguists, three material experts and three design experts, as well as data analysis of learning outcomes by calculating N-gain. The results of the study stated that (1) teaching materials based on the learning cycle method developed are valid, used to improve students' mathematics learning outcomes in grade VIII SMP North Tapanuli Regency, (2) teaching materials based on the learning cycle method developed practically, used to improve student mathematics learning outcomes in grade VIII SMP North Tapanuli Regency, (3) teaching materials based on the learning cycle method developed effectively, used to improve student mathematics learning outcomes in grade VIII SMP North Tapanuli Regency, (4) teaching materials based on the learning cycle method developed can improve student learning outcomes in grade VIII SMP North Tapanuli Regency. The acquisition of calculated results or N-Gain value of 0.64 with the category of sufficient or good learning improvement results.